2022
DOI: 10.29303/jppipa.v8i5.1890
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Praktikum Berbasis Excel Materi Pemeriksaan Karbohidrat (Glukosa, Sukrosa Dan Fruktosa) Untuk Meningkatkan Keterampilan Proses Sains

Abstract: Keterampilan proses sains berpotensi membangun kompetensi dasar mahasiswa. Terdapat banyak faktor yang mempengaruhi keterampilan ini salah satunya penggunaan media yang tepat. Pengembangan media praktikum berbasis excel merupakan salah satu solusi untuk menyelesaikan permasalahan ini. Tujuan penelitian untuk meningkatkan keterampilan proses sains mahasiswa dalam melakukan praktikum. Penelitian ini berdesain Research and Development (R&D )dengan populasi 132 orang dengan sampel berjumlah   66   orang   meng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Furthermore, (Melita et al, 2023) also revealed that learning media has an important role in learning activities because of its role as an intermediary for teachers in delivering messages or information, this is so that learning materials can be easily understood by students well. Learning media also acts as a useful supporting tool to clarify the meaning of a message conveyed, so that the role of the media can achieve learning objectives well (Andayani et al, 2022). The results of the student response questionnaire in figure 4.10 also show that students become more enthusiastic in participating in learning activities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, (Melita et al, 2023) also revealed that learning media has an important role in learning activities because of its role as an intermediary for teachers in delivering messages or information, this is so that learning materials can be easily understood by students well. Learning media also acts as a useful supporting tool to clarify the meaning of a message conveyed, so that the role of the media can achieve learning objectives well (Andayani et al, 2022). The results of the student response questionnaire in figure 4.10 also show that students become more enthusiastic in participating in learning activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to noise, individual factors that can affect occupational fatigue include blood glucose levels (Sulistyowati et al, 2019) and body mass index (Mansouri-yachou et al, 2019;Muriyati et al, 2023). Blood glucose levels are the body's main source of energy (Andayani et al, 2022;Safrida et al, 2023). Stable and sufficient blood glucose levels are essential to maintain adequate energy levels during intense physical or mental activities.…”
Section: Introductionmentioning
confidence: 99%